Monocyte-derived Langerhans cells express Delta-like 4 induced by peptidoglycan and interleukin-4 mediated suppression - Ono, Rei; Maeda, Kohei; Tanioka, Toshihiro; Isozaki, Takeo (Frontiers in Immunology, 2025)
T cells contribute to immunotherapy and autoimmune pathogenesis and Langerhans cells (LCs) have a substantial ability to activate T cells. In vitro-generated monocyte-derived LCs (Mo-LCs) are useful models to study LC function in autoimmune diseases and to test future LC-based immunotherapies. Although dendritic cells (DCs) expressing high levels of Delta-like 4 (DLL4+ DCs), which is a member of the Notch ligand family, have greater ability than DLL4− DCs to activate T cells, the induction method of human DLL4+ DCs has yet to be determined. The aim of this study is to establish whether Mo-LCs express DLL4 and establish the induction method of antigen presenting cells, which most potently activate T cells, similar to our previously established induction method of human Mo-LCs. We compared the ratios of DLL4 expression and T cell activation via flow cytometry among monocyte-derived cells, which have a greater ability than the resident cells to activate T cells. Here, we discovered that Mo-LCs expressed DLL4, which most potently activated T cells among monocyte-derived cells, and that Mo-LCs and DLL4 expression were induced by DLL4, granulocyte macrophage colony-stimulating factor, and transforming growth factor-β1. Additionally, peptidoglycan was required for DLL4 expression, whereas interleukin-4 repressed it. These findings provide insights into the roles of DLL4-expressing cells such as DLL4+ Mo-LCs in human diseases, which will assist with the development of more effective therapeutic strategies in the future.